Beyond Sanctions: Progressive Legal Strategies for Victim Empowerment and Violence Prevention - Labaka, Albri; Hi Abas, Gunawan (Universitas Muhammadiyah Yogyakarta, 2025)
Domestic violence (DV), particularly when experienced by wives as victims of physical, psychological, sexual, and economic abuse, remains a deeply concerning legal and social phenomenon in Indonesian society. This study examines the normative dimensions of DV against women through the lens of progressive legal theory and the framework of positive law. The findings reveal that uncontrolled jealousy, economic pressure, and alcohol consumption are among the primary triggers of domestic violence. Such violence manifests in physical, sexual, psychological, and financial forms, all of which have a profound impact on victims' overall well-being. (UU PKDRT) provides a clear legal foundation for victim protection, including through protective orders. However, from a progressive legal perspective, the response to domestic violence must go beyond a rigid and normative application of the law by embracing a more humane, empathetic, and victim-oriented approach. Law enforcement officials, including judicial bodies, are expected to consider the psychological and mental condition of victims in handling such cases. Furthermore, effective recovery requires multi-sectoral involvement, including legal advocates, healthcare professionals, social workers, and volunteer companions, to ensure that victims receive holistic protection encompassing legal, emotional, and social support